Who Are We Really? Latin American Family, Local and Micro-Regional Histories, and Their Impact on Understanding Ourselves - Delgadillo, Roberto C. (Seminar on the Acquisition of Latin American Library Materials, 2016)
Selected papers from the annual conference of the Seminar on the Acquisition of Latin American Library Materials